2010
DOI: 10.1097/eja.0b013e3283335cee
|View full text |Cite
|
Sign up to set email alerts
|

Duration of fluid fasting and choice of analgesic are modifiable factors for early postoperative delirium

Abstract: Duration of preoperative fluid fasting and the choice of intraoperative analgesic are risk factors for postoperative delirium, and their modification provides a promising approach to reduce the incidence of postoperative delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 21 publications
1
88
2
10
Order By: Relevance
“…Like other studies 7,24,28 , delirium patients were older than non-delirium patients. These patients have a reduced physical reserve that can predispose them to higher severity of illness and, therefore, higher incidence of POD.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Like other studies 7,24,28 , delirium patients were older than non-delirium patients. These patients have a reduced physical reserve that can predispose them to higher severity of illness and, therefore, higher incidence of POD.…”
Section: Discussionmentioning
confidence: 58%
“…In this study using ICDSC, considered very sensitive tool for screening of delirium, we found a POD incidence slightly inferior of that found by other authors. [18][19][20][21][22][23][24] . This lower incidence may be explained by the demographic characteristics of the study population with younger patients and a better preoperative status (patients with lower ASA-PS and lower RCRI).…”
Section: Discussionmentioning
confidence: 99%
“…6 Puasa minum preoperatif juga merupakan salah satu faktor yang berpengaruh terhadap kejadian delirium pascaoperasi saat di ruang pemulihan (11%) maupun di bangsal (4,2%) selain pemberian analgesia selama operasi. 3,7 Panduan puasa preoperatif yang diterapkan di berbagai negara diperbolehkan minum clear fluids sampai dengan 2 jam sebelum operasi. Pemberian minuman kaya karbohidrat 2 jam sebelum operasi ternyata tidak meningkatkan volume gaster atau meningkatkan keasaman, tetapi pemberian ini terbatas pada pasien yang tidak memiliki gangguan motilitas usus seperti gastroparesis, obstruktif mekanis, gastroesofageal refluks, dan morbid obese.…”
Section: Pendahuluanunclassified
“…11 Puasa yang terlalu lama dapat merugikan dan dapat memengaruhi kondisi fisik serta psikologi pasien seperti ketidaknyamanan, 13 cemas, nyeri kepala, dehidrasi, mual muntah, hipovolemia, hipoglikemia, 5,6 bahkan delirium pascaoperasi. 7 Selama pasien menjalani puasa preoperatif, dapat terjadi haus, lapar, cemas, mengantuk, dan pusing. 3,15 Puasa preoperatif yang lama meningkatkan jalur katabolik sehingga dapat meningkatkan komplikasi.…”
Section: 2unclassified
“…Breytingar verða á líkamsástandi og umhverfi einstaklingsins við skurðaðgerðir og geta ýmsir útleysandi áhaettu-þaettir, svo sem verkir, truflanir á vökva-og saltbúskap, fasta og gjörgaesludvöl, fylgt í kjölfarið. 1,30 Bráð skurðaðgerð getur haft aukna haettu á óráði í för með sér umfram valaðgerð 19 Þeir einstaklingar sem eru útsettari fyrir óráði vegna hás aldurs, heilabilunar eða annarra undirliggjandi áhaettuþátta þurfa mun minna áreiti til að fá óráð en þeir sem ekki hafa undirliggjandi áhaettuþaetti. 22,27,28 Tafla I. Samanburður einkenna óráðs og heilabilunar.…”
Section: áHaettuþaettir óRáðs Eftir Skurðaðgerðunclassified